Efek Ekstrak Buah Delima Merah terhadap Jumlah Fibroblas di Ligamen Periodontal Daerah Tarikan Gigi Tikus Wistar Selama Pergerakan Gigi Ortodonti - Dina Nuur Rosyiidah; Happy Harmono; Herniyati Herniyati (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
Orthodontic useful for repairing the arrangement of teeth by remodeling the alveolar bone and periodontal ligament and then fibroblast proliferation will occur. Fibroblast play a role in the formation of collagen fibers that will connect teeth to bones. Orthodontic takes a long time so it takes a method to speed it up. One of them can use red pomegranate extract which contains antioxidants. This Research purpose to analyze the effect and impact of the duration of administration of red pomegranate extract on the number of fibroblasts in the 1st, 2nd, and 3rd weeks of the periodontal ligament in the tooth-tensioning area of wistar rats during orthodontic tooth movement. 36 rats divided into 6 groups: the group with orthodontic appliance installation without red pomegranate extract for 1 week (A), 2 weeks (B), and 3 weeks (C), and the orthodontic appliance installation group with red pomegranate extract administration for 1 week. weeks (D), 2 weeks (E) and 3 weeks (F). The provision of orthodontic mechanical forces by placing a ligature on the right M1 tooth and both maxillary incisors. Then the M1 is moved mesial using a tension gauge to produce a force of 11.5 gF with Ni-Ti closed coil spring. When the rats were euthanized and histology was made with Haematoxylin Eosin (HE) staining. Fibroblasts were observed by using microscope with 400 magnification in 3 fields of view. The average number of fibroblasts in all groups (A, B, C, D, E and F) increased and in the LSD test it was found that between groups there was a significant difference because it had a p-value ≤ 0.05 Red pomegranate extract increase the number of fibroblasts in the periodontal ligament tension area and there is an increase in the number of fibroblasts in the 1st week to the 3rd week.